The Role of Postoperative Irradiation in the Treatment of Locally Recurrent Incompletely Resected Extra-Abdominal Desmoid Tumors. (2004) - Fontanesi, James; Mott, Michael P.; Kraut, Michael J.; Lucas, David P.; Miller, Peter R.
Abstract : Background : To define the efficacy of postoperative irradiation in patients with recurrent extra-abdominal desmoid tumors in whom surgical intervention has resulted in microscopically or grossly positive surgical margins. Methods : A retrospective analysis was performed on all patients referred to the department of radiation oncology at the Detroit Medical Center with a diagnosis of recurrent extra-abdominal desmoid tumor. This analysis includes all patients seen from 1 January 1990 through 31 December 1999. A total of 11 patients were treated to 13 sites. Ten had microscopically positive margins and three had gross residual disease. Three patients were noted to have multifocal disease at the time of initial representation. Local control, survival, follow-up, and subsequent development of new tumors are measured from the last day of treatment with irradiation. Results : Thirteen sites were treated. Seven patients had received chemotherapy/hormonal therapy prior to surgery and/or irradiation. The most commonly used drug was tamoxifen ( n =6). The type of radiation delivered included external beam irradiation alone ( n =3), combined external beam irradiation and brachytherapy ( n =4), brachytherapy alone ( n =3) and 252-Cf neutron brachytherapy alone ( n =3). Follow-up has ranged from 29 to 115 months (median=76 months). Three patients have failed locally at 17, 24 and 29 months. One of these was treated for gross residual disease. No patient has died of tumor-related causes. Salvage at the failed sites was possible in twom of three with re-irradiation using external neutrons and/or aggressive surgical intervention and systemic therapy. Complications were most often noted to include decrease range in motion, especially in joint areas, and skin reactions which were normal in presentation. In one site there was development soft tissue necrosis. Conclusion : Based on our experience we recommend postoperative irradiation for all recurrent extra-abdominal desmoid lesions with microscopically or grossly positive surgical margins. Furthermore, patients with recurrent desmoid tumors involving the bony structures of the hand or feet are poor candidates for brachytherapy alone. For patients with extremity lesions, brachytherapy may be a reasonable treatment option provided adequate margins around the tumor bed are covered. The continued recommended use of irradiation in this group of patients is warranted.